A comparative study of different diatomite-supported TiO2 composites and their photocatalytic performance for dye degradation. Issue 37 (8th August 2016) - Zhang, Guangxin; Wang, Bin; Sun, Zhiming; Zheng, Shuilin; Liu, Shushu
Abstract: Three kinds of diatomites as catalyst carriers were adopted to prepare supported TiO2 catalysts by a typical hydrolysis–deposition method. The prepared composites were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, N2 adsorption–desorption, scanning electron microscopy transmission electron microscopy, UV–vis diffuser reflectance, and chemical oxygen demand. The photocatalytic properties of composites were determined using rhodamine B, methyl orange, and methylene blue as target pollutants under UV light irradiation. A comparative study on the photocatalytic properties of composite catalysts was carried out. It is indicated that the catalytic performance of TiO2 /diatomite is significantly influenced by the physicochemical properties of diatomite supports. Compared with pure TiO2, the TiO2 /diatomite composites exhibited smaller crystalline size of TiO2 and better dispersibility, which induced higher specific surface area and better photo-degradation efficiency. The highest activity of the photocatalyst should be attributed to the acid-activated support, which provided more active sites for the degradation reaction. Besides, the durabilities of catalysts were also investigated. The experimental results indicated that the prepared composite is a promising material for the wastewater treatment for its good photocatalytic property and reusability.